ANN Based Fault Classifier and Fault Locator for Double Circuit Transmission Line - Atul A, Kale; Navita G, Pandey (International Journal of Computer Sciences and Engineering, 2025)
Accurate and fast fault detection, classification and location is very important from the service restoration and reliability point of view. However in case of double circuit transmission line due to mutual coupling effect this may result in poor discrimination between faulty and healthy line. This paper presents an artificial neural network based fault classifier and locator for double circuit transmission line. The neural network was trained by various sets of data available from simulation of model for different faults conditions. The obtained simulation result shows the proposed system works satisfactorily.